Social sustainability in manufacturing: where are we? - Blandino, Graziana; Montagna, Francesca (International journal of production research, 2025)
The definition of Social Sustainability and the methods used for its assessment are still changing, especially concerning Manufacturing. Recent industrial revolutions have transformed workers' roles and these changes need to be considered for social sustainability development. This systematic literature review provides a comprehensive view of the State of the Art of Social Sustainability in Manufacturing (SSM) at the plant level of production systems. The selected contributions have provided knowledge about the current definitions and assessment of SSM, its drivers, barriers and industrial implications, especially regarding technologically advanced environments. However, neither an official outline nor an assessment method of this concept has yet emerged. Therefore, this paper discusses how SSM can be abstracted into a three-dimensional space, defined by boundaries, the subject of social analysis and the research methodology. Dimensional space and boundaries are combined in frameworks to support manufacturing actors in developing customised SSM definitions and evaluations, while leaving the research methodology for further investigation. Such frameworks may contribute to increasing society's awareness of social sustainability and designing new norms. In addition, they may guide companies in reaching sustainability goals and academia in pursuing new research directions.